Customer Experience, Journey Mapping, Touchpoint, dan Service Blueprint dalam Meningkatkan Kepuasan Pelanggan - Mohammad Haydi Pane; Siti Syarifah; Arfiani Yulianti Fiyul (CV. ITTC INDONESIA, 2026)
This article provides a comprehensive examination of the concept of Customer Experience and its role in enhancing customer satisfaction, loyalty, and relationship expansion. Using a qualitative literature-based approach, the study analyzes the importance of Customer Journey Mapping and Service Blueprinting as strategic tools for understanding and managing customer interactions. The discussion highlights key elements such as touchpoints, interaction quality, personalization, data security, brand consistency, as well as emotional impact and peak-end effects on customer engagement. The findings indicate that effective management of customer experience—particularly through journey mapping—has a positive relationship with customer satisfaction and expansion behaviors. The study also explores the evolution of customer experience, crisis response design, and their relevance in maintaining sustainable customer–company relationships across various industries.